Rh-catalyzed sequential oxidative C–H activation/annulation with geminal-substituted vinyl acetates to access isoquinolines1. Issue 68 (4th September 2015) - Chu, Haoke; Sun, Song; Yu, Jin-Tao; Cheng, Jiang
<x xml:space="preserve">Abstract</x> The concise synthesis of 3-substituted or non-C3-substituted isoquinolines through Rh-catalyzed sequential oxidative C–H activation/annulation with geminal-substituted vinyl acetates was developed.